2003
DOI: 10.1258/095646203767869110
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of risky sex of young men after release from prison

Abstract: A longitudinal study of demographic and behavioural characteristics associated with risky sexual behaviours of young men after release from prison. One hundred and six men were interviewed in prison and at one week and six months after release. Overall, 37% reported a previous sexually transmitted disease (STD) diagnosis. In the 30 days before incarceration, 33% had had sex with a risky partner, and 59% had had multiple female sex partners. After release, 38 (36%) men reported having had risky sex (>or=2 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 4 publications
6
67
1
Order By: Relevance
“…The significance of this relationship endured multiple adjustments for preceding confounders and additional post hoc analyses controlling for baseline levels of unprotected vaginal sex. These findings are consistent with previous research linking incarceration with unprotected sex 6,7,17,33 but build on them by defining a temporal ordering of exposure and outcomes. Furthermore, this is the first known study to highlight a temporal relationship between arrest and sexual risk.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The significance of this relationship endured multiple adjustments for preceding confounders and additional post hoc analyses controlling for baseline levels of unprotected vaginal sex. These findings are consistent with previous research linking incarceration with unprotected sex 6,7,17,33 but build on them by defining a temporal ordering of exposure and outcomes. Furthermore, this is the first known study to highlight a temporal relationship between arrest and sexual risk.…”
Section: Discussionsupporting
confidence: 90%
“…Widespread within criminal justice populations are drug abuse and mental illness, which have repeatedly been linked to sexual risk behaviors. [9][10][11][12][13][14][15] Among male offenders, correlates of sexual risk-taking include past sexual or physical victimization, 16 unstable housing, 17 poverty and unemployment, 18 and social stress linked to race and socioeconomic status. 19 In a previous cross-sectional study of men in drug treatment, we found that recent arrest or incarceration was associated with several sexual risk behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…34 Patient education about HIV prevention should extend to nontraditional settings, such as prisons and jails, and continue through re-entry into the community since immediate release from these facilities represents one of the greatest risk periods for injection drug use and risky sexual behavior. 35,36 This study has notable limitations. We sampled participants from two rural counties in one state and only included AAs in our FGs, thereby limiting external validity to other groups and settings.…”
Section: Discussionmentioning
confidence: 98%
“…12,13 After the incarceration, absence of a stable sex partner with stress of reintegration 66 may lead newly released prisoners to engage in increased levels of multiple and concurrent partnerships. 9,[15][16][17][18][19] A number of important study limitations should be noted. First, since this study was cross-sectional, we do not know the temporal relationship between incarceration and sexual risk behavior and hence cannot conclude that incarceration contributed to high-risk sex partnerships.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] The absence of a stable partner, together with the stress of reintegration after incarceration, may lead newly released prisoners to engage in increased levels of multiple partnerships, including concurrent partnerships (multiple partnerships that overlap in time). 9,[15][16][17][18][19] Partnership concurrency is considered to be a particularly important determinant of STI/HIV transmission. 20 There is evidence that incarceration history is associated with high-risk sex partnerships including multiple and concurrent partnerships; 15,17,[21][22][23][24][25] however, most studies have been performed in small convenience samples.…”
mentioning
confidence: 99%